2018
DOI: 10.1002/pon.4759
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy‐associated cognitive impairments in Korean cancer patients: Risk factors and functional outcome

Abstract: Significant cognitive decline occurred during active chemotherapy; attention to cognitive impairment should be given in the early phase of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Studies have shown that up to 90% of tumor patients have received chemotherapy [7] . Adverse reactions after chemotherapy can lead to persistent and chronic oxidative stress, psychological stress, and psychological disorders, which will lead to cancer-related fatigue and reduce the quality of life of patients [8,9] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that up to 90% of tumor patients have received chemotherapy [7] . Adverse reactions after chemotherapy can lead to persistent and chronic oxidative stress, psychological stress, and psychological disorders, which will lead to cancer-related fatigue and reduce the quality of life of patients [8,9] …”
Section: Introductionmentioning
confidence: 99%
“…[7] Adverse reactions after chemotherapy can lead to persistent and chronic oxidative stress, psychological stress, and psychological disorders, which will lead to cancer-related fatigue and reduce the quality of life of patients. [8,9] As a new complementary and alternative therapy, music therapy is easily accepted by cancer patients. [10] Music therapy treats patients' physical or mental diseases through rhythm and tone, helps patients better express their emotions and promotes inner emotional communication.…”
Section: Introductionmentioning
confidence: 99%